Arterial hypoxaemia and its impact on coagulation: significance of altered redox homeostasis. Issue 9 (4th June 2015) - Fall, Lewis; New, Karl J; Evans, Kevin A; Bailey, Damian M
Abstract : Aims: Arterial hypoxaemia stimulates free radical formation. Cellular studies suggest this may be implicated in coagulation activation though human evidence is lacking. To examine this, an observational study was designed to explore relationships between systemic oxidative stress and haemostatic responses in healthy participants exposed to inspiratory hypoxia. Results: Activated partial thromboplastin time and international normalised ratio were measured as routine clinical biomarkers of coagulation and ascorbate free radical (A − ) as a direct global biomarker of free radical flux. Six hours of hypoxia activated coagulation, and increased formation of A −, with inverse correlations observed against oxyhaemoglobin saturation. Conclusions: This is the first study to address the link between free radical formation and coagulation in vivo. This 'proof-of-concept' study demonstrated functional associations between hypoxaemia and coagulation that may be subject to redox activation of the intrinsic pathway. Further studies are required to identify precisely which intrinsic factors are subject to redox activation.